Earl's well that ends well - Ashford, Jane (Sourcebooks Casablanca, 2021)
"Arthur Shelton, Earl of Macklin, has helped four young noblemen recover from grief and find love, but he's learned to live his own life as a widower. Yet when he returns home after traveling, his estate feels too empty, and he quickly heads to London. There, he encounters Teresa Alvarez de Granada, a charming Spanish noblewoman and is immediately entranced. There is no room for earls in the quiet, safe life Teresa has finally found for herself. The earl might be charming and handsome, but she knows firsthand how dangerous attraction can be. The more determined Teresa is to discourage Arthur, the more entangled they get, and it's only a matter of time before her respect for him starts to feel a lot like love."--